Pengaruh Pemahaman Sistem Akuntansi Keuangan Daerah (SAKD), Pemanfaatan Teknologi Informasi Dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pada Pemerintahan Desa Kecamatan Besitang - M. Putra Abdul Rozak Barus; Hendra Harmain; Khairina Tambunan (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the effect of understanding the Regional Financial Accounting System (SAKD), the use of information technology, and internal control on the quality of financial reports in the Besitang District Village Government. This research uses quantitative methods with an associative approach, data collection techniques using questionnaires, the number of samples in this research is 45 people from the Village Work Unit (SKPD) who are involved in financial preparation reports at the Besitang District village/district office. The sampling technique uses a saturated sampling technique. Data were analyzed using multiple linear regression methods. The results of this research show that Understanding the Regional Financial Accounting System (SAKD) partially has a significant effect on the Quality of Financial Reports in the Besitang District Village Government, while the partial use of Information Technology and Internal Control does not have a significant effect on the Quality of Financial Reports in the Besitang District Village Government. Understanding the Regional Financial Accounting System (SAKD), Utilization of Information Technology, and Internal Control simultaneously have a positive and significant effect on the Quality of Financial Reports in the Besitang District Village Government.